Strategic Leadership: Conceptual Significance and Theoretical Patterns (قضايا سياسية, 2025)
This study aims to analyze the conceptual foundations and theoretical patterns of strategic leadership as a central element in state management within a turbulent strategic environment. The research adopts a descriptive–analytical approach of an inductive nature, through a review of relevant literature and theories, linked to contemporary developments in leadership patterns. The study examines the distinction between the leader and leadership, the historical roots of strategic leadership, and its modern conceptual evolution, in addition to analyzing the main leadership styles, including transformational, transactional, autocratic, and democratic, and their impact on strategic performance. The findings indicate that effective strategic leadership is based on clarity of vision, institutional flexibility, the capacity for innovation, and the ability to influence human and social capital, as it constitutes an interactive process between leaders and followers that contributes to political stability, sustainable development, and enhances the state’s capacity for strategic adaptability.